Addressing weight loss management in obese gout patients: guidance for future trials - Robin Christensen; Tobias Haugegaard; Melanie B. Morillon; Henrik Gudbergsen; Henning Bliddal; Lisa K. Stamp (Exploration of Musculoskeletal Diseases)
Obesity is widely recognized as being associated with both the onset and advancement of gout, exerting a detrimental effect on health outcomes in society. In the realm of gout management, theoretical frameworks support weight loss as a beneficial strategy for people impacted by overweight or obesity. Existing empirical evidence is limited to a handful of predominantly observational studies with low methodological rigor. A recent exploratory clinical trial which included 61 people with obesity and gout randomly allocated participants to either an intensive diet group (n = 29) or a control diet group (n = 32). After 16 weeks, a significant difference in body weight change was observed between the intensive diet group and the control diet group [−7.7 kg (95% confidence interval −10.7 to −4.7)]. Although the results leaned towards favoring a low-energy diet, differences in changes in serum urate (SU) levels and fatigue between the groups could not be confirmed. For the majority of individuals who lose weight a key challenge is long term maintenance. Novel agents such as glucagon-like peptide-1 receptor agonists (GLP-1Ras) have a role in weight loss and its maintenance. In this manuscript we propose what we consider the ideal target trial for weight loss in gout. We envision a two-year randomized trial with participants allocated to either a GLP-1Ra or placebo and evaluated and monitored over a two-year period.